Fase-Fase Tektonik Pembentuk Ruang Mineralisasi Emas Di Daerah Selogiri Wonogiri - Widagdo, Asmoro (Jenderal Soedirman University, 2008)
Metallic mineral deposits in Tumbu Hill and the surrounding area of Selogiri, Wonogiri Regency in Central Java Province formed relate to some process of tectonism. The metallic mineral deposits in this area are the result of epi thermal processes, filling previousl y existing fractures. This fracture system is closely related to structures that are the result of regional tectonic phases. Veins in the research area strike in many different directions and each has distinct metallic content from the others. This research utilizes the know ledge of result of magmatism process and also regional tectonic phases which formed the fractures where the veins are located and relationship with veins direction that have potential metallic content especially gold and silver.